Pengaruh Kemiringan Spindel Dan Kecepatan Putaran Spindel Terhadap Getaran Mesin Frais Universal Knuth UFM 2 - Romiyadi Romiyadi (Jurnal Sains dan Ilmu Terapan, 2018)
— In milling process with spindle slope, the milling process requires energy from milling machine. The greater the spindle slope estimated to be the greater energy required by the milling machine. Therefore, the machining vibration that occurs was estimated to be very big. This study aimed to determine the influence spindle slope to machining vibration in milling machine with variations of spindle speed. This study used Milling Machine Knuth Universal UFM 2 with vertical milling approach. The slope spindle used was 300, 450 and 600. The machining process parameters varied was the spindle speed, while feed and depth of the cut were constant. The study results show that the greater the spindle slope, the greater the machining vibration on the up milling process and the down milling processes for all spindle slope. Similarly with the influence of spindle speed to machining vibration in milling process.